The Role of Metabolism in Heart Failure and Regeneration - Bae, Jiyoung; Paltzer, Wyatt G.; Mahmoud, Ahmed I. (Frontiers in Cardiovascular Medicine, 2021)
Heart failure is the leading cause of death worldwide. The inability of the adult mammalian heart to regenerate following injury results in the development of systolic heart failure. Thus, identifying novel approaches toward regenerating the adult heart has enormous therapeutic potential for adult heart failure. Mitochondrial metabolism is an essential homeostatic process for maintaining growth and survival. The emerging role of mitochondrial metabolism in controlling cell fate and function is beginning to be appreciated. Recent evidence suggests that metabolism controls biological processes including cell proliferation and differentiation, which has profound implications during development and regeneration. The regenerative potential of the mammalian heart is lost by the first week of postnatal development when cardiomyocytes exit the cell cycle and become terminally differentiated. This inability to regenerate following injury is correlated with the metabolic shift from glycolysis to fatty acid oxidation that occurs during heart maturation in the postnatal heart. Thus, understanding the mechanisms that regulate cardiac metabolism is key to unlocking metabolic interventions during development, disease, and regeneration. In this review, we will focus on the emerging role of metabolism in cardiac development and regeneration and discuss the potential of targeting metabolism for treatment of heart failure.